Role of infection and T cells in disease pathogenesis in a model of Alzheimer's disease - McManus, Róisín M. (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2015)
Alzheimer's disease (AD) is a progressive neurodegenerative disease characterised by deposits of amyloid-β (Aβ) and neurofibrillary tangles. It has been suggested that inflammatory changes are associated with disease, however, it has not been established if these are a consequence of ongoing neurodegeneration or whether inflammation itself contributes to disease pathogenesis. T cells have been reported in the AD brain and clinical trials involving immunization with Aβ induced increased T cell infiltration into the brain and meningoencephalitis in some patients. In this study, the effect of Aβ-specific T cells was assessed in vitro and in vivo.
Keywords: Biochemistry & Immunology, Ph.D.; Ph.D. Trinity College Dublin